(untitled) (Web of Teachers: Inderscience Research, 2026)
Color-based metaphors represent a fundamental aspect of human cognition, structuring abstract concepts through sensory experiences of color. This study addresses the challenges of semantic transformations in color metaphors during translation, highlighting how cultural and linguistic differences affect their rendering. Drawing on cognitive metaphor theory, the research employs comparative analysis of English color metaphors and their equivalents or adaptations in Uzbek and other languages, supplemented by examples from literary and corpus data. The analysis reveals that while universal mappings (e.g., RED for anger or danger) facilitate direct transfer, culture-specific associations often require semantic shifts, substitution, or explicitation to preserve pragmatic impact. Effective translation of color metaphors demands cognitive awareness and contextual sensitivity, balancing fidelity to source meaning with target-culture acceptability. This contributes to improved translation strategies in cross-linguistic communication